Nanotechnology: A reality for diagnosis of HCV infectious disease. Issue 1 (January 2020) - Arca-Lafuente, Sonia; Martínez-Román, Paula; Mate-Cano, Irene; Madrid, Ricardo; Briz, Verónica
Summary: Hepatitis C virus (HCV) is the primary etiologic agent of liver cirrhosis or hepatocellular carcinoma. HCV elevated infection rates are mostly due to the lack of an accurate and accessible screening and diagnosis, especially in low- and middle-income countries. Conventional HCV diagnostic algorithm consists of a serological test followed by a nucleic acid test. This sequence of tests is time consuming and not affordable for low-resource settings. Nanotechnology have introduced new promising tests for the diagnose of infectious diseases. Based on the employment of nanoparticles and other nanomaterials which lead to highly sensitive and specific nanoscale tests, most of them target pathogen genome. Implementation of nanoscale tests, which are affordable, portable and easy to use by non-specialized personal, would improve HCV diagnosis algorithm. In this review, we have summed up the current emerging nanotechnology tools, which will improve actual screening and treatment programs, and help to reach HCV elimination proposal.